Closure of Large, Complex Defects after Oncologic Neurosurgery with a Free Myoperitoneal Flap - de Weerd, Louis; Kloster, Roar; Walter, Clemens (Journal of Reconstructive Microsurgery, 2013)
Extensive and complex defects after neurosurgical oncologic resections including dura are a challenge, as watertight closure is of paramount importance. This article illustrates the usefulness of a free myoperitoneal flap in closure of such a defect when located at the skull base or cranium. The vascularized peritoneum appears to be an excellent biological replacement for the dura and the well-vascularized muscle promotes wound healing and obliterates dead space.
Keywords: musculoperitoneal flap; dura:skull base; cerebrospinal fluid leakage; esthesioneuroblastoma